Microcontroller based Bidirectional Energy Metering for Domestic User - Mallikarjun G Hudedmani; Vishwanath M. Soppimath; Chaitanya. K. Jambotkar; Digamber. S. Albur (Journal of Electronic Design Engineering, 2017)
The present energy scenario is greatly alarming the energy consumers to conserve as fossil fuels are going to deplete shortly. In this regard the renewable energy systems are really gaining momentum. Solar and wind roof top fittings are becoming popular choice for the domestic user based on their financial affordability. Solar panels generate energy to power a building’s electrical systems. In most cases, builders acknowledge that the solar panels installed on the roof will not always be sufficient for the building’s electrical needs, so the building is also connected to the main utility grid. However, sometimes during clear days the solar panels generate surplus power beyond the needs of the building. At these times, the surplus power is exported into the main utility grid. Most utility companies offer credits to buildings that export power in this manner. “Bi-directional Meter” means a consumer meter for measuring, indicating and recording quanta of electricity flowing in opposite directions (export to the licensee’s distribution system and import by the consumer from distribution system) in Kwh including any other quantity as per the requirement. Net metering / bidirectional metering record both import and export energy values giving prime focus on utilizing self produced electricity by renewable energy sources and excess or surplus to be sold to utilities or grid. It results into reduction of electricity bills. Solar photovoltaic system is used significantly in net metering. The design of microcontroller based bidirectional energy meter is low cost, affordable to consumer for domestic application and efficient. The current work focusses on the development of one of the type of bidirectional metering which accounts the net usage, export and the monetory exchange. The intelligent controller makes use of the measuring setup and controls all the major activities of the proposed work.